Variant rs4149584 (R92Q) of the TNFRSF1A gene in patients with familial multiple sclerosis - U. Gomez-Pinedo; J.A. Matías-Guiu; L. Torre-Fuentes; P. Montero-Escribano; L. Hernández-Lorenzo; V. Pytel; P. Maietta; S. Alvarez; I. Sanclemente-Alamán; L. Moreno-Jimenez; D. Ojeda-Hernandez; N. Villar-Gómez; et al. (Neurología (English Edition))
Introduction: Genomic studies have identified numerous genetic variants associated with susceptibility to multiple sclerosis (MS); however, each one explains only a small percentage of the risk of developing the disease. These variants are located in genes involved in specific pathways, which supports the hypothesis that the risk of developing MS may be linked to alterations in these pathways, rather than in specific genes. We analyzed the role of the TNFRSF1A gene, which encodes one of the TNF-α receptors involved in a signaling pathway previously linked to autoimmune disease. Methods: We included 138 individuals from 23 families including at least 2 members with MS, and analyzed the presence of exonic variants of TNFRSF1A through whole-exome sequencing. We also conducted a functional study to analyze the pathogenic mechanism of variant rs4149584 (-g.6442643C > G, NM_001065.4:c.362 G > A, R92Q) by plasmid transfection into human oligodendroglioma (HOG) cells, which behave like oligodendrocyte lineage cells; protein labeling was used to locate the protein within cells. We also analyzed the ability of transfected HOG cells to proliferate and differentiate into oligodendrocytes. Results: Variant rs4149584 was found in 2 patients with MS (3.85%), one patient with another autoimmune disease (7.6%), and in 5 unaffected individuals (7.46%). The 2 patients with MS and variant rs4149584 were homozygous carriers and belonged to the same family, whereas the remaining individuals presented the variant in heterozygosis. The study of HOG cells transfected with the mutation showed that the protein does not reach the cell membrane, but rather accumulates in the cytoplasm, particularly in the endoplasmic reticulum and near the nucleus; this suggests that, in the cells presenting the mutation, TNFRSF1 does not act as a transmembrane protein, which may alter its signaling pathway. The study of cell proliferation and differentiation found that transfected cells continue to be able to differentiate into oligodendrocytes and are probably still capable of producing myelin, although they present a lower rate of proliferation than wild-type cells. Conclusions: Variant rs4149584 is associated with risk of developing MS. We analyzed its functional role in oligodendrocyte lineage cells and found an association with MS in homozygous carriers. However, the associated molecular alterations do not influence the differentiation into oligodendrocytes; we were therefore unable to confirm whether this variant alone is pathogenic in MS, at least in heterozygosis. Resumen: Intriducción: En estudios genómicos se han identificado numerosas variantes genéticas asociadas con la susceptibilidad a la esclerosis múltiple (EM); sin embargo, cada una de ellas explica solo un pequeño porcentaje del riesgo de desarrollar la enfermedad. Estas variantes se localizan en genes implicados en vías específicas, lo que apoya la hipótesis de que el riesgo de desarrollar EM puede estar relacionado con alteraciones en estas vías, más que en genes específicos. Analizamos el papel del gen TNFRSF1A, que codifica para uno de los receptores de TNF-α implicados en una vía de señalización que ha sido previamente relacionada con enfermedades autoinmunes. Métodos: Incluimos a 138 individos de 23 familias que incluían al menos 2 miembros con EM y analizamos la presencia de variantes exónicas de TNFRSF1A mediante la secuenciación del exoma completo. También realizamos un estudio funcional para analizar el mecanismo patogénico de la variante rs4149584 (-g.6442643C > G, NM_001065.4:c.362 G > A,R92Q) por transfección plasmídica en células de oligodendroglioma humano (HOG), las cuales se comportan como células de linaje oligodendrocitario; se utilizó marcaje de proteínas para localizar la proteína dentro de las células. También analizamos la capacidad de las células HOG transfectadas para proliferar y diferenciarse en oligodendrocitos. Resultados: La variante rs4149584 se encontró en 2 pacientes con EM (3,85 %), un paciente con otra enfermedad autoinmune (7,6 %) y en 5 individuos no afectados (7,46 %). Los 2 pacientes con EM y variante rs4149584 eran portadores homocigotos y pertenecían a la misma familia, mientras que los individuos restantes presentaron la variante en heterocigosis. El estudio de células HOG transfectadas con la mutación mostró que la proteína no llega a la membrana celular, sino que se acumula en el citoplasma, particularmente en el retículo endoplásmico y cerca del núcleo; esto sugiere que, en las células que presentan la mutación, TNFRSF1 no actúa como una proteína transmembrana, lo que puede alterar su vía de señalización. El estudio de proliferación y diferenciación celular encontró que las células transfectadas siguen siendo capaces de diferenciarse en oligodendrocitos y, probablemente, todavía sean capaces de producir mielina, sin embargo, presentan una menor tasa de proliferación que las células silvestres. Conclusiones: La variante rs4149584 está asociada con el riesgo de desarrollar EM. Analizamos su papel funcional en células de linaje oligodendrocitario y encontramos una asociación con la EM en portadores homocigóticos. Sin embargo, las alteraciones moleculares asociadas no influyen en la diferenciación a oligodendrocitos; por lo tanto, no hemos podido confirmar si esta variante por sí sola es patógena en la EM, al menos en la heterocigosis.